Surface modification of PDMS with PEG-SILANE for enchanced adhesion and proliferation of mesenchyml stem cells - Poovitha Natarajan (2014)
Poly(dimethylsiloxane) has gained attention in the bio-industry in the recent decade for its widely used application in the fabrication of microfluidic devices. However, PDMS surface is highly hydrophobic in nature making it less biocompatible for mammalian cell.. Three PDMS surfaces were prepared; unmodified PDMS, plasma treated PDMS, Plasma treated, PEG-Silane modified PDMS. Water-droplet contact-angle measurements were made. The unmodified PDMS surface an average contact angle of 100.128 ± 0.430 o while the plasma treated PDMS has a contact angle measurement of 14.756 ± 2.480 o The contact angle measurement for PEG-Silane modified PDMS surface was 82.965 ± 4.811o The plasma treated PDMS has the highest surface wettability This clearly indicates that plasma treatment is very efficient in modifying the surface to me very hydrophilic. However, PEG-Silane was not able to fully efficient in preserving the hydrophilic surface obtained from the plasma treatment due to uneven coating on the surface. Future works could focus on aiming to form even PEG-Silane coats on the PDMS surface and proceed on with cell culture to perform cell proliferation and adhesion assays.